Ex Situ Carbon Mineralization for CO2 Capture Using Industrial Alkaline Wastes—Optimization and Future Prospects: A Review - Hamideh Hamedi; Giovanna Gonzales-Calienes; Jalil Shadbahr (Clean Technologies, 2025)
Carbon mineralization has attracted great interest as a promising strategy to achieve a decarbonized pathway by 2050. Despite the significant environmental and economic promise associated with using industrial solid waste for carbon mineralization, the scale-up application of this approach is limited due to its low reactivity and relatively high cost. A clear understanding of the detailed mechanisms governing various carbonation techniques is needed to achieve high CO2 conversion efficiency. This review can provide valuable insight into carbon mineralization pathways, advantages and challenges, and potential feedstocks. Factors affecting reaction kinetics, and thereby carbonation efficiency, are also discussed. Then, we focus on the research progress of the most representative industrial solid wastes for CO2 mineralization, process conditions, and their carbonation potential. Lastly, a market analysis of the precipitated carbonate products is provided to assess economic feasibility for practical applications.